FIRST RECORD OF THE BEETLE Trachyderes succinctus (CERAMBYCIDAE) ON THE PLANT Senna reticulata (FABACEAE) IN IQUITOS, PERU - ZÁRATE GÓMEZ, Ricardo (2023)
This study documents for the first time the presence of the beetle Trachyderes succinctus (Cerambycidae) on the plant Senna reticulata (Fabaceae) in the city of Iquitos, Peru. The sample consisted of three beetle larvae collected from within the branches of the plant, which were reared in controlled environments until reaching adulthood. The adult beetle individuals and plant samples were identified using specialized keys. T. succinctus shows a preference for plant species in the Fabales order, and this finding expands our knowledge of its relationship with different species. This study provides valuable information about the interaction between the beetle and the plant in the Peruvian Amazon.